Professional linkages at the transition to school: Boundaries and linked ecologies. Issue 4 (May 2021) - Dockett, Sue; Perry, Bob
The transition to school brings early childhood and school educators together in the common aim of promoting a positive start to school. This transition also highlights the boundaries and professional linkages that contribute to this aim. Conceptualising boundary spaces as sites of professional identity construction and negotiation, we explore professional linkages between early childhood education and care and school educators during transitions to school, usingAbbott's linked ecologies framework. To do this, we examine data from two studies, exploring the proposition that collaboration – in the forms of professional networks and transition statements (shared documentation) – have the potential to act as linkages across the ecologies of early childhood education and care and school education. Our conclusions support this potential but note that the nature and impact of these linkages is variable. Further, we argue that contradictions and tensions in the perceived professional roles of educators are evident within these linkages.